Dense arrays of cobalt nanorods as rare-earth free permanent magnets. Issue 7 (28th January 2016) - Anagnostopoulou, E.; Grindi, B.; Lacroix, L.-M.; Ott, F.; Panagiotopoulos, I.; Viau, G.
Abstract : We demonstrate in this paper the feasibility to elaborate rare-earth free permanent magnets based on cobalt nanorods assemblies with energy product ( BH )max exceeding 150 kJ m −3 . Abstract : We demonstrate in this paper the feasibility to elaborate rare-earth free permanent magnets based on cobalt nanorods assemblies with energy product ( BH )max exceeding 150 kJ m −3 . The cobalt rods were prepared by the polyol process and assembled from wet suspensions under a magnetic field. Magnetization loops of dense assemblies with remanence to a saturation of 0.99 and squareness of 0.96 were measured. The almost perfect M ( H ) loop squareness together with electron microscopy and small angle neutron scattering demonstrate the excellent alignment of the rods within the assemblies. The magnetic volume fraction was carefully measured by coupling magnetic and thermogravimetric analysis and found in the range from 45 to 55%, depending on the rod diameter and the alignment procedure. This allowed a quantitative assessment of the ( BH )max values. The highest ( BH )max of 165 kJ m −3 was obtained for a sample combining a high magnetic volume fraction and a very large M ( H ) loop squareness. This study shows that this bottom-up approach is very promising to get new hard magnetic materials that can compete in the permanent magnet panorama and fill the gap between the ferrites and the NdFeB magnets.